A note on motivated cognition and discriminatory beliefs - Lasse Stötzer; Florian Zimmermann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
In this note, we provide evidence that motivated reasoning can be a source of discriminatory beliefs. We employ a representative survey experiment where we exogenously manipulate the presence of a need for justification of anti-social behavior towards an out-group. We provide causal evidence that survey participants devalue members of an out-group to justify taking away money from the group. Our results speak to a long-standing debate on the causes of racism and discrimination and suggest an important role of motivated cognition.
Keywords: D01; 330; discrimination; stereotypes; racism; motivated reasoning; beliefs